ENTREPRENEURIAL THINKING IN WOMEN AND ITS ROLE IN THE SOCIAL DEVELOPMENT OF SOCIETY (Scientific journal of the Fergana State University, 2023)
In this article, the content, specifics and improvement of Women's entrepreneurial thinking in the period of implementation of the development strategy of the new Uzbekistan of our society was studied scientifically and theoretically. We tried to socially-philosophically analyze the development, strengthening of the social, cultural, economic and legal foundations of women's entrepreneurial thinking, as well as the importance in the development of our country.